Exploring Product Return Behavior in E-Commerce : Insights from an Emerging Market Context - Kar, Brajaballav; Das, Piyusa Pritiparanna; Mohapatra, Sasmita (Indian Journal Marketing, 2024)
Purpose : In contrast to return behavior, consumer purchasing behavior is thoroughly investigated. Returns have increased in tandem with the growth of online shopping through e-commerce sites, particularly in emerging nations like India. The present study aimed to determine whether there are any prevailing behavioral features associated with customer returns, given the disproportionate number of returns that India receives in comparison to other nations. The body of existing studies has not sufficiently examined product returns resulting from internet sales. Investigating the expanding e-commerce sector and the unprofitability of these businesses in the context of emerging markets requires research.Methodology : A systematic online questionnaire survey was used to gather information on a variety of topics related to returns after purchases, including delivery experiences, product dissonance, information search, product attributes and categories, and demographics. Outcome factors included the size of the returns and the frequency of returns.Findings : This research concluded that the following elements can be used to explain product return behavior in online purchases: situational circumstances, impulse, experimenting with new products, volition, unethical behavior, seasonal purchases, purchases prompted by promotions, and enforced options. In addition to these, dissonance, delivery encounters, information behavior, and productspecific factors $1 (Ball played a big role in online purchase returns. The frequency, variety, and mechanism of reimbursement of returns for internet purchases varied greatly.Originality : To have a better understanding of the return behavior, this research took into account factors such as income, monthly expenses, and spending on online goods.Managerial Implications : Understanding the return behavior could help influence customer purchases, returns, and retention. Managers could control and manage the factors influencing returns at a desired level.s
Keywords: DeliveryInformation Search; Product; Online PurchaseReturnBehavior